Tata Kelola Keuangan Pada Lembaga Perkreditan Desa (LPD) Di Desa Adat Bakas - Cahyani, Putu Resa Putri; I Wayan Sudiana; Ni Wayan Alit Erlina Wati (UNHI Press, 2025)
The role of LPDs is growing day by day, this cannot be separated from the public's trust in Village Credit Institutions. In its activities, LPD cultivates capital through savings, deposits and loans from the community, then in its activities LPD is able to provide effective loans to people in need, so a situation must be created where the community (village residents) feel safe in saving their money, either in the form of savings or deposits. . This research was carried out with the aim of finding out how financial governance is implemented at the Bakas Traditional Village Credit Institution.The informants in this research were the supervisory body, secretary, treasurer and mobile savings officer. The number of informants in this study was 7 people using the interview method, namely 3 supervisors, 1 secretary, 1 treasurer and 2 mobile savings officers. This research is qualitative research where research data is obtained through an interview process with respondents.The research results show that the financial governance of the Bakas Traditional Village LPD has not implemented the principles of good corporate governance such as transparency, accountability, responsibility, independence, equality and fairness in accordance with the provisions. Based on the results of existing research, it can be suggested that in the future, the Bakas Traditional Village LPD is very important to be able to maintain good LPD financial governance so that corruption no longer occurs within the LPD.